Does the presence of posterior comminution modify the treatment and prognosis in capitellar and trochlear fractures? Study performed on 45 consecutive patients. (November 2018) - Marinelli, Alessandro; Cavallo, Marco; Guerra, Enrico; Ritali, Alice; Bettelli, Graziano; Rotini, Roberto
Abstract: Introduction: Only few case series of capitellar and trochlear fractures have been reported. Some of them assume that the presence of a posterior comminution (type B according to Dubberley classification) can represent a negative risk factor for treatment and prognosis respect to the type A cases (without posterior comminution). Nevertheless, how this parameter impacts the treatment and the prognosis has never been quantified before. Materials and methods: All the capitellar and trochlear fractures treated from 2007 to 2015 have been retrospectively reviewed. The presence of posterior comminution on a pre-operative CT-scan was correlated to the surgical technique, to the timing of initiation of rehabilitation and to clinical outcomes. Results: 45 Consecutive patients have been selected, 17 not presenting a posterior comminution (type A), and 28 with posterior comminution (type B). In all the type A fractures a lateral approach (Kocher o Kocher extensile) was used and the fragment fixation was always performed using only screws. Elbow replacement or olecranon osteotomy were performed only to treat type B fractures. Augmented fixations, using plates and k-wires, or prosthetic replacement have been used only in type B fractures. The post-operative immobilization was significantly inferior for type A fracture. Better results have been obtained in type A fractures: mean MEPI score was 86 in type A and 73 in type B, the range of motion was significatively higher in type A both in flexion-extension and in pronation-supination. In type B fractures a significant higher number of complications have been observed (64% vs 29%) along with more reoperations. Discussion: The study has confirmed that, even without considering the extension of the fracture on the coronal plane, the presence of posterior comminution represents an evident negative risk factor, influencing the surgical approach and treatment, the fixation technique, the post-operative rehabilitation, the clinical outcomes, the complications and re-operation rates. Conclusions: The analysis of the present case series shows how the treatment and the outcomes can be significantly anticipated based on the presence or absence of posterior comminution. Patients with type A fracture are more likely treated with a Kocher approach, screw fixation, an early rehabilitation is performed. In type A fractures better outcomes and low complications rate are expected.